"Sturdy Boulders that Protect the Realm" Early Medieval Chinese Thinkers on Decentralized Governance. (1st January 2018) - Villagran, Ignacio
Abstract : The period between the formal end of the Han dynasty in 220ce and the reestablishment of unified imperial authority in the Sui-Tang period (late sixth centuryce ) is considered one of political fragmentation and recurrent military conflict. During three centuries, several kingdoms and short-lived dynasties were established and destroyed, either by military conquest or by court intrigues and coups. In this context, many political thinkers of the time looked back to the long rule of the Han as a time of peace and prosperity, and argued that it was the institutions of centralized governance that propped the dynasty's long-lasting reign. Against this view, a handful of thinkers claimed that the Zhou-style system of investiture offered several advantages to secure the permanence of the ruling house and improve the governance of the realm. Among them, the Wei dynasty thinker Cao Jiong argued that the Zhou system was superior to centralized rule both in moral and military terms, while the Jin dynasty scholar Lu Ji discussed the benefits and problems of relying mostly on kin for controlling the realm. By identifying the key ideas in these writings in relation to the historical context of the early medieval period in China, I will challenge the longstanding assumption that post-Han thinkers advocated for the institutions of centralized administration over those of decentralized governance.